“Snapping, sharing and receiving blame”: A systematic review on psychosocial factors of victim blaming in non-consensual pornography - Senthil Amudhan; Manoj Kumar Sharma; Nitin Anand; Jemimah Johnson (Industrial Psychiatry Journal, 2024)
Non-consensual pornography has become a growing concern, with potentially negative consequences for the victims. Victims of revenge porn are more likely to be blamed, and understanding why and how blame is attributed toward victims of non-consensual pornography is crucial to support them and reduce the negative consequences. This study aimed to explore and synthesize the existing evidence on victim blaming in non-consensual pornography and the underlying psychosocial factors within the context of attribution framework. A comprehensive systematic review was conducted across four databases namely PubMed, ProQuest, Google Scholar, and Scopus for English-language studies published from April 2012 to June 2022. Data from the selected studies were extracted and collated into the review matrix. Among the 22 full-text reviews, 10 records that met the eligibility criteria were included in the final review. Two themes namely “Culture and morality” and “gendered differences in attributions of blame” were derived from a thematic synthesis of 10 studies and reflected the psychosocial underpinnings of victim blaming. The review highlighted how cultural narratives and perceived immorality play a major role in how attributions are placed on self or others for victim blaming in “non-consensual pornography.” Blame attributions emerging from gender stereotyping and gendered responsibilization within cultural and societal contexts were found to impact self-blame and compound victimization in non-consensual pornography. The study findings implicated that recognizing psychosocial underpinnings of victim blame attribution in revenge porn would allow for evolving suitable legislative and policy responses for designing effective educative and preventative strategies.